Shift From Warming Slowdown to Rewarming of Winter Sea Surface Temperature in the South China Sea Before and After 2013 - Zhaoyun Wang; Shiqiang Yao; Yanyan Wang; Hanjin Liu; Yimin Zhang; Wenjing Dong; Xing Liu; Yu Han; Xiaoran Shi (Advances in Meteorology)
The winter sea surface temperature (SST) in the South China Sea (SCS) before and after 2013 experienced a shift from warming slowdown to rewarming, and the interdecadal variability in the northern SCS was more pronounced than that in the southern SCS. The heat budget results indicate that the warming slowdown of SST in the northern SCS was primarily attributed to negative oceanic advection during 1997–2012. During 2013–2019, the reduction of evaporation played a dominant role in the rewarming of SST in the northern SCS, while the increase of short-wave radiation and positive oceanic advection played secondary roles. Further analysis suggests that the shift from warming slowdown to rewarming in the northern SCS may be related to the changes in the location and intensity of the North Pacific subtropical high. The southward shift of the eastern Pacific subtropical high (EPSH) during 1997–2012 resulted in anomalous easterly winds in the equatorial eastern Pacific Ocean and caused the weakening of Kuroshio intrusion into the SCS, which was the main mechanism leading to the warming slowdown of winter SST in the northern SCS. During 2013–2019, the enhancement of the western Pacific subtropical high (WPSH) caused the weakening of the East Asian winter monsoon (EAWM) and the reduction of cloud cover, resulting in the enhancement of the net surface heat flux into the ocean, which was the primary mechanism leading to the rewarming of winter SST in the northern SCS. Meanwhile, the northward shift of the EPSH led to the increase of Kuroshio intrusion into the SCS due to the anomalous westerly winds in the equatorial eastern Pacific Ocean, which also contributed to the rewarming of winter SST in the northern SCS.